2016
DOI: 10.11159/mhci16.103
|View full text |Cite
|
Sign up to set email alerts
|

Getting Back To Basics: Bimanual Interaction on Mobile Touch Screen Devices

Abstract: The availability, and popularity, of touch screen tablets is drastically increasing with over 30% of internet users now owning one. However the lack of bimanual interaction in touch screen tablets is presenting product designers with serious challenges. Several attempts have been made to facilitate bimanual interaction in such products but results are not comparable to that of their non-mobile cousins, e.g. laptops. This paper presents the finding of a group collaboration aimed at prototyping a mobile touch sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…In particular, people tend to perform more productive activities when a computer is at hand. Having access to mobile phones, however, did not trigger more productive activities, perhaps due to a lack of professional software and a large screen for complex work [e.g., 21,53]. Some of our data supports this.…”
Section: Leisure Activities As the Most Performedsupporting
confidence: 57%
“…In particular, people tend to perform more productive activities when a computer is at hand. Having access to mobile phones, however, did not trigger more productive activities, perhaps due to a lack of professional software and a large screen for complex work [e.g., 21,53]. Some of our data supports this.…”
Section: Leisure Activities As the Most Performedsupporting
confidence: 57%
“…Each input device, whether a touchscreen or a mouse, offers a variable user experience which may lead to different results for similar actions or tasks [2,3]. Comparative studies between mice and touchscreen found mice more effective [4].…”
Section: Introductionmentioning
confidence: 99%
“…(Balagtas-Fernandez et al, 2009). Interface design is further complicated, as mobile phones are used by a wide range of people with different goals anytime in any location (Huang, 2009). This also makes usability an even more important quality attribute of software applications for mobile phones (Treeratanapon, 2012).…”
Section: Introductionmentioning
confidence: 99%